ANALISIS FAKTOR – FAKTOR YANG MEMENGARUHI INTENSI BERWIRAUSAHA PADA MAHASISWA UNIVERSITAS BRAWIJAYA - Zelly Sidi Zamzami (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Abstract: The goal of this research is to investigate entrepreneurial intention of university students and factors which influence the intention based on model that was developed by Linan as an application of Theory of Planned Behavior (TPB). The data’s were analyzed with Structural Equation Model (SEM). The sample was 232 university students from 4 majors which are Management, Industry Engineering, English Literature, and Statistics with various year of study that had passed entrepreneurship courses. The findings of the research shows that entrepreneurial intention is directly and positively affected by Personal Attitude and Perceived Behavioral Control. The Subjective Norm does not directly influence the entrepreneurial intention but indirectly and positively influence the entrepreneurial intention through Personal Attitude and Perceived Behavioral Control. Keywords: Entrepreneurial intentions, Theory of Planned Behavior